Patronage Networks and Power Disparities: The Legacy of Political Patronage in Indonesia's Governance and Democracy - Kurniawan, Rahmat (JPP (Jurnal Politik Profetik), 2025)
This study examines the role and impact of political patronage on Indonesia’s governance and its contribution to the power disparity. It offers strategies to mitigate patronage’s negative effects and promote effective governance, highlighting its persistence as a sign of Indonesia’s still-developing democracy. Using a qualitative descriptive method and literature review, data collection includes primary sources like research reports and surveys, and secondary sources such as journal articles, books, and news. Key search terms include patronage, clientelism, corruption, oligarchy, and money politics. Findings reveal that patronage remains widespread through vote buying, selective distribution of goods and services, and misuse of public funds for elections. Historically, patronage dates back to pre-independence (tribute systems), post-independence (oligarchic consolidation), and reformasi (non-merit-based governance). Under the New Order, patronage networks became deeply institutionalized, hindering democratic progress. Today, patronage persists in regional elections, where incumbents act as patrons appointing officials, while civil servants seek career advancement through these networks. The social, political, and economic entrenchment of patronage weakens institutions, erodes public trust, reduces competency in governance, and limits fair, pro-people policies. To address these challenges, this study recommends strengthening anti-corruption bodies, enhancing political party funding regulations, ensuring merit-based appointments, and improving the electoral system for greater inclusivity and accountability.